Respuesta :

Answer:

[tex]Y=-\frac{1}{3}(x+6)^2+7[/tex]   [Vertex form]

Step-by-step explanation:

Given function:

[tex]Y=-\frac{1}{3}x^2-4x-5[/tex]

We need to find the vertex form which is.,

[tex]y=a(x-h)^2+k[/tex]

where [tex](h,k)[/tex] represents the co-ordinates of vertex.

We apply completing square method to do so.

We have  

[tex]Y=-\frac{1}{3}x^2-4x-5[/tex]

First of all we make sure that the leading co-efficient is =1.

In order to make the leading co-efficient is =1, we multiply each term with -3.

[tex]-3\times Y=-3\times\frac{1}{3}x^2-(-3)\times4x-(-3)\times 5[/tex]

[tex]-3Y=x^2+12x+15[/tex]

Isolating [tex]x^2[/tex] and [tex]x[/tex] terms on one side.

Subtracting both sides by 15.

[tex]-3Y-15=x^2+12x-15-15[/tex]

[tex]-3Y-15=x^2+12x[/tex]

In order to make the right side a perfect square trinomial, we will take half of the co-efficient of [tex]x[/tex] term, square it and add it both sides side.  

square of half of the co-efficient of [tex]x[/tex] term = [tex](\frac{1}{2}\times 12)^2=(6)^2=36[/tex]

Adding 36 to both sides.

[tex]-3Y-15+36=x^2+12x+36[/tex]

[tex]-3Y+21=x^2+12x+36[/tex]

Since [tex]x^2+12x+36[/tex] is a perfect square of [tex](x+6)[/tex], so, we can write as:

[tex]-3Y+21=(x+6)^2[/tex]

Subtracting 21 to both sides:

[tex]-3Y+21-21=(x+6)^2-21[/tex]

[tex]-3Y=(x+6)^2-21[/tex]

Dividing both sides by -3.

[tex]\frac{-3Y}{-3}=\frac{(x+6)^2}{-3}-\frac{21}{-3}[/tex]

[tex]Y=-\frac{1}{3}(x+6)^2+7[/tex]   [Vertex form]